Exploring risk factors of short-term readmission in heart failure patients: A cohort study - Niu, Xiao Na; Wen, He; Sun, Nan; Zhao, Ran; Wang, Ting; Li, Yan (Frontiers in Endocrinology, 2022)
Background: The risk of all-cause mortality in patients with heart failure (HF) has been studied previously. Readmission risk of HF patients was rarely explored. So, we aimed to explore early warning factors that may influence short-term readmission of HF patients. Methods: The data of this study came from a HF database in China. It was a retrospective single-center observational study that collected characteristic data on Chinese HF patients by integrating electronic medical records and follow-up outcome data. Our study included 26 variables, 1727 patients with CH patients were finally included in our study. Results: In this study, the proportion of HF patients with New York Heart Association (NYHA) class II, III and IV patients were 17.20 %, 52.69 % and 30.11 %. The proportion of patients with readmission within 6 months and readmission within 3 months were 38.33 % and 24.20 %. Multivariate logistic regression showed that NYHA class (PIII = 0.028, PIV < 0.001), diabetes (P = 0.002), Cr (P = 0.003) and RDW-SD (P = 0.039) were risk factors for readmission within 6 months of HF patients. NYHA class (PIII = 0.038, PIV < 0.001), CCI (P = 0.033), Cr (P = 0.012), UA (P = 0.042) and Na (P = 0.026) were risk factors for readmission within 3 months of HF patients. Conclusions: Our study implied risk factors of short-term readmission risk in patients with HF, which may provide policy guidance for the prognosis of patients with CH.